AURKA inhibitor-induced PD-L1 upregulation impairs antitumor immune responses - Meng, Bi; Zhao, Xuan; Jiang, Shuchang; Xu, Zijian; Li, Sijin; Wang, Xu; Ma, Wen; Li, Liantao; Liu, Dan; Zheng, Junnian; Peng, Hui; Shi, Ming (Frontiers in Immunology, 2023)
Tumor immunotherapy targeting PD-L1 has emerged as one of the powerful tools for tumor therapy. Numerous studies indicate that tumor-targeted drugs critically have an influence on the interaction between the immune system and tumors by changing the expression of PD-L1 during cancer treatments, which is beneficial for the combination of immunotherapy. Our study provided the evidence for improving the drug regimen and exploring more optimal drug combinations in tumor targeted therapy and immunotherapy. The expression of PD-L1 on SKBR3, MDA-MB-231, MCF7, 4T1, MC38 and B16 cells was evaluated by flow cytometry after treatment with six preclinical targeted drugs (ARN-509, AZD3514, Galeterone, Neratinib, MLN8237 and LGK974). We found that AURKA inhibitor MLN8237 promoted the expression of PD-L1 in a time- and concentration-dependent manner while exerted its antitumor effect. Knockdown of AURKA by using the specific siRNA or CRISPR-Cas9 technology could block the upregulation of PD-L1 in SKBR3 cells. We also proved that MLN8237-induced PD-L1 was mainly associated with the upregulation of p-STAT3. In the 4T1-breast tumor xenograft model, CD3+ and CD8+ T cells infiltrated in tumor tissues decreased after treatment with MLN8237. When treated with MLN8237 in combination with anti-PD-L1 antibody, the volumes of tumor were significantly reduced and accompanied by increasing the infiltration of CD3+ and CD8+ T cells in colorectal cancer xenograft tumor model. Our data demonstrated that MLN8237 improved the effect of immunology-related therapy on tumor cells by interacting with anti-PD-L1 antibody, which contributed to producing creative sparks for exploring the possible solutions to overcoming drug resistance to tumor targeted therapy.